A tunable blue–cyan dual emission phosphor in Ca4−xLu2xHf1−xGe3O12:Bi3+ via forming segregation structure for WLEDs. Issue 12 (25th August 2022) - Piao, Siqi; Wang, Yichao; Zhang, Jinsu; Zhang, Xizhen; Wu, Danyang; Cao, Yongze; Li, Xiangping; Chen, Baojiu
Abstract: White light‐emitting diodes (WLEDs) are always fabricated by a combination of the near‐ultraviolet (n‐UV)‐emitting LED chip with tricolor emitting phosphors. However, improving the color rendering index (CRI) is limited due to the absence of cyan composition for common commercial combinations. Based on this, a series of blue–cyan dual‐peaks emission Ca4− x Lu2 x Hf1− x Ge3 O12 (CLHGO):Bi 3+ phosphors with unique adjustability are developed by the solid solution design strategy. All the samples belong to the garnet structure with the Ia 3 d space group. Two relatively independent segregation structures [Ca4 HfGe3 O12 ] and [Ca3 Lu2 Ge3 O12 ] are established in the samples. When Bi 3+ ions enter into the highly symmetrical hexagon coordination environment, a special phenomenon appears that the emission peaks consist of two stabilized narrowband emission bands at 435 and 475 nm, their intensity ratio could change continuously with the increase of solid solubility. All these results are confirmed by means of excitation and emission spectra, first principles calculation and decay curves. The Ca3.4 Lu1.2 Hf0.4 Ge3 O12 :Bi 3+ sample, with a high efficiency around 84.1% and an excellent thermal stability (65.6%@150°C), is chosen as the optimal sample to improve the blue and cyan compositions for full spectrum emission. Using the Ca3.4 Lu1.2 Hf0.4 Ge3 O12 :Bi 3+, commercial green (Ba, Sr)2 SiO4 :Eu 2+ phosphor, and commercial red CaAlSiN3 :Eu 2+ phosphor on a 360‐nm n‐UV LED chip to fabricate WLED, which successfully bridge the cyan gap and the CRI value of the as‐fabricated warm‐white LED reaches 90.2. The previous results confirmed that CLHGO:Bi 3+ phosphors have promising application prospect in the development of n‐UV‐pumped warm‐white LEDs with high‐CRI values. The unique property performance originating from independent segregation structures provides more reference for the research on photoluminescence mechanism. Abstract : The emission spectra consist of two stable narrow band emission peaks (435 and 475 nm) because of the existence of two relatively dependent segregation structure. Achieving the ratio of blue and cyan tunable by changing the composition. The full‐spectrum emission of 90.2 color rendering index was obtained by using our phosphor.